2018
DOI: 10.1386/crre.9.1.41_1
|View full text |Cite
|
Sign up to set email alerts
|

‘I like knowing when the zombies arrive, I won’t be naked’: Young women and leisure handcrafting in the United States

Abstract: In a modern world where technology is readily available, handwork is sometimes taken for granted, hidden or viewed with suspicion by outsiders, without fully understanding the benefits of engaging in such mindful activity. Younger women face challenges of trying to fit into a hobby subculture that is stereotypically reserved for older women (45 years and older). In-person and online qualitative research with 32 young women leisure crafters (aged 18–44 years) attest to some of the difficulties of trying to enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The material resources to which makers had access transformed how they produced PPE. Reflective of how younger and/or less‐financially well‐off sewists regularly manage inter‐household conflicts that can emerge because they do not have spaces specifically dedicated to their craft (Stalp, 2006; Stalp et al., 2018), younger makers living with others often indicated that the members of their households were upset that they had “taken over” common areas to produce PPE. When asked on the questionnaire how members of her household felt about her efforts to make masks, a white woman in her 30s living in the Eastern United States explained:
My husband is mostly very supportive (and has even spent some time helping to cut elastic) although he gets tired of all the materials being in the way and sometimes seems a little dismissive when I prioritize it over other things he sees as more high priority.
…”
Section: Setting the Stage: Ppe Shortages During A Neoliberal Pandemi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The material resources to which makers had access transformed how they produced PPE. Reflective of how younger and/or less‐financially well‐off sewists regularly manage inter‐household conflicts that can emerge because they do not have spaces specifically dedicated to their craft (Stalp, 2006; Stalp et al., 2018), younger makers living with others often indicated that the members of their households were upset that they had “taken over” common areas to produce PPE. When asked on the questionnaire how members of her household felt about her efforts to make masks, a white woman in her 30s living in the Eastern United States explained:
My husband is mostly very supportive (and has even spent some time helping to cut elastic) although he gets tired of all the materials being in the way and sometimes seems a little dismissive when I prioritize it over other things he sees as more high priority.
…”
Section: Setting the Stage: Ppe Shortages During A Neoliberal Pandemi...mentioning
confidence: 99%
“…Technologies and bodies are saturated with gendered meanings that inform the who, what, where, why, and how of social reproduction. Quilters, for example, navigate meanings that associate technologies such as fabrics, needles, thread, and sewing machines with domesticated femininity as they engage in social reproduction (Stalp, 2015; Stalp et al., 2018). Such meanings have material consequences for gendered bodies as they are physically contorted to align with institutional and interpersonal expectations for how particular bodies ought to look, move, smell, and sound (Hochschild, 1983; Kang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ample feedback regarding the impact of crochet on multiple areas of the girls' lives is observed as noted in Table 1. The merging of fibers with high tech or math encouraged STEAM learning (Stalp et al, 2018) and more interest in "math in real life." Three girls expressed that crochet connected to math and STEAM by including fabric in STEM creativity conversations and raising the visibility of making the connections of handicrafts to the hard sciences (Stalp et al, 2018).…”
Section: Stem Learningmentioning
confidence: 99%
“…The literature also showed that crochet can foster creativity in girls. Studies reported crochet as a great outlet for creativity (Myers 2011), and the old world craft of crochet can be used as a tool for young women to expand their creativity (Pickrem, 2019;Stalp et al, 2018). In addition, Kijima et al (2021) present research on design thinking and integrating artistic approaches in relation to the importance of STEAM learning and how it complements STEM.…”
Section: Introductionmentioning
confidence: 99%
“…We use the term "makers" because respondents often referred to themselves as such. Study participants also regularly utilised machine sewing and 3D printing equipment, and libraries, entrepreneurial centres, and universities often include these technologies in "maker spaces" (Stalp 2020;Stalp et al 2018).…”
Section: Introductionmentioning
confidence: 99%